P876 Prevalence of Clostridium difficile infection among hospitalised inflammatory bowel disease patients in Greece. (16th January 2018) - Viazis, N; Pontas, C; Belesiotou, E; Karmiris, K; Dimas, I; Fragaki, M; Paspatis, G; Banasa, M; Drygiannakis, I; Koutroubakis, I; Maraki, S; Moschovis, D; et al.
Abstract: Background: Clostridium difficile ( C. difficile ) is the leading cause of antibiotic-associated colitis and nosocomial diarrhoea. Patients with inflammatory bowel disease (IBD) are at increased risk of developing C. difficile infection (CDI); however, data on the prevalence of CDI in Greece are limited. We sought to determine rates of CDI among hospitalised IBD patients in major tertiary referral hospitals in Greece. Methods: We performed a retrospective analysis of stool culture results from hospitalised patients investigated for diarrhoea that were tested for CDI from January till December 2016. A rapid immunoenzymatic (EIA) assay (C.diff Quik check, Complete, Techlab, Blacksburg, VA, USA) was used to test for glutamate dehydrogenase (GDH). Toxins A and B were also sought in positive samples, in order to confirm CDI. Finally, CDI prevalence in IBD patients was compared with non-IBD patients. Results: In total 6932 patients were tested for CDI while hospitalised. Among them, 894 patients were found positive for GDH (12.89%), while 339 were also found positive for C. Difficile toxin (4.89%). Therefore, the prevalence of CDI among all hospitalised patients was 1.6/1000 patient-days. Among them, there were 401 IBD patients presenting with diarrhoea and tested for CDI. Sixty-two patients were found positive for GDH (15.46%), while 30 were also found positive for C. difficile toxin (7.48%). Therefore, the prevalence of CDI in IBD patients was 2.5/1000 patient-days. The prevalence of CDI among IBD hospitalised patients was significantly higher than non-IBD hospitalised patients (30/401 vs. 309/6531, p = 0.013). Among the 30 IBD patients with CDI, there were 14 men and 16 women, with a mean age of 46 years. Eighteen of them had ulcerative colitis (E1 = 2, E2 = 3, E3 = 13) and 12 Crohn's disease (A2L1B1 = 3, A2L2B1 = 3, A2L3B1 = 3, A3L1B1 = 2, A3L3B3 = 1). Six of them were receiving biologics, 3 were receiving corticosteroids (one with azathioprine and one with 5-ASA), 9 were on azathioprine monotherapy and 12 on 5-ASA monotherapy. CDI was successfully treated with metronidazole and/or vancomycin in all cases. Conclusions: Data from IBD referral tertiary Greek hospitals show that CDI prevalence is higher in hospitalised IBD patients than those without IBD. CDI is a growing public health issue among hospitalised IBD patients, prompting the need for better preventative measures, as well as for early detection and treatment.